Evaluasi Unsur – Unsur Pengendalian Internal Dalam Penerimaan Kas Pada CV. Adhika Putra Mandiri - Nurbani Masjidha, Rifdha; Priono, Hero (Rifa'Institute, 2023)
The company's internal control is the main thing because it has an important role in preventing and detecting fraud and protecting company assets, both tangible and intangible. This study aims to determine the internal control system of cash receipts at CV. Adhika Putra Mandiri has been running well or not and whether it is in accordance with internal control. This research uses descriptive qualitative method. Data collection techniques using the method of observation, interviews and documentation. The results of the analysis and research show that CV. Adhika Putra Mandiri has implemented an internal control system for cash receipts but its application to the company is still not good because there are still weaknesses. The weaknesses are that the organizational structure is not fully structured, there are still multiple assignments, proof of cash receipts has not been stamped with a